The Impact of Arabic Reading Comprehension on Students’ Writing Skills in Selected Senior Arabic Secondary Schools in Jigawa State (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study explores the impact of Arabic reading comprehension on students’ writing skills in selected senior Arabic secondary schools in Jigawa State. Through a comprehensive analysis involving reading and writing tests administered to 250 students, the research aims to identify the relationship between students' reading proficiency and their writing abilities. Findings indicate a moderate level of reading comprehension but below-average writing skills. The absence of a standardized curriculum and insufficient teacher training are highlighted as significant factors affecting students' performance. Recommendations include the development of a unified curriculum, enhanced teacher training, and increased resource provision.